d,l-Methadone causes leukemic cell apoptosis via an OPRM1-triggered increase in IP3R-mediated ER Ca2+ release and decrease in Ca2+ efflux, elevating [Ca2+]i - JungKwon Lee (Nature Portfolio, 2021)
Abstract The search continues for improved therapy for acute lymphoblastic leukemia (aLL), the most common malignancy in children. Recently, d,l-methadone was put forth as sensitizer for aLL chemotherapy. However, the specific target of d,l-methadone in leukemic cells and the mechanism by which it induces leukemic cell apoptosis remain to be defined. Here, we demonstrate that d,l-methadone induces leukemic cell apoptosis through activation of the mu1 subtype of opioid receptors (OPRM1). d,l-Methadone evokes IP3R-mediated ER Ca2+ release that is inhibited by OPRM1 loss. In addition, the rate of Ca2+ extrusion following d,l-methadone treatment is reduced, but is accelerated by loss of OPRM1. These d,l-methadone effects cause a lethal rise in [Ca2+]i that is again inhibited by OPRM1 loss, which then prevents d,l-methadone-induced apoptosis that is associated with activation of calpain-1, truncation of Bid, cytochrome C release, and proteolysis of caspase-3/12. Chelating intracellular Ca2+ with BAPTA-AM reverses d,l-methadone-induced apoptosis, establishing a link between the rise in [Ca2+]i and d,l-methadone-induced apoptosis. Altogether, our findings point to OPRM1 as a specific target of d,l-methadone in leukemic cells, and that OPRM1 activation by d,l-methadone disrupts IP3R-mediated ER Ca2+ release and rate of Ca2+ efflux, causing a rise in [Ca2+]i that upregulates the calpain-1-Bid-cytochrome C-caspase-3/12 apoptotic pathway.